Sensitivity and chaos on product and on hyperspatial semiflows. Issue 1 (2nd January 2021) - Thakur, Rahul; Das, Ruchi
ABSTRACT: We study stronger forms of sensitivity on the arbitrary product of semiflows on Hausdorff uniform spaces. Moreover, Devaney chaos, Poincaré chaos, and their related properties are studied on product semiflows. Furthermore, we study relations between the chaos-related properties of a semiflow and that of its induced hyperspatial semiflow. Some results regarding stronger forms of sensitivity are also obtained on hyperspatial semiflows.